Depiction of a Surasundari figure - Temples of India Project Team (Jio Institute, 2024)
The portrayal of this surasundari (celestial damsel), on the northern wall, encapsulates the nurturing essence of femininity. Standing gracefully, she cradles a baby in her arms, although the faces of both mother and child are obscured. The mother has a voluptuous figure adorned with elaborate ornaments. The child is depicted holding her breast, symbolizing the bond of maternal care and sustenance.